Impact of Particulate Size During Deep Loading on DPF Management - Ornella Chiavola; Giancarlo Chiatti; Nidal Sirhan (Applied Sciences, 2019)
Wall-flow particulate filters are a required emission control device to abate diesel emission in order to comply with current regulations. DPFs (diesel particulate filters) are characterized by high filtration efficiency—but in order to avoid deterioration of power and performance, they are required to cause low values of backpressure. The periodical oxidation of collected particle allows for the reestablishment of the ideal flow conditions. Studies highlighted that the regeneration event has an important impact on engine emission, since it is responsible for the emission of a large number of smaller particles. From these considerations, the importance of optimizing the DPF management for what concerns both filtration and regeneration mechanisms arises. The present paper focuses on the loading process of the filter. A filtration model was implemented, based on the ‘unit-collector’ and fluid-dynamic approaches, known as valid modelling techniques. The model was used to predict trapped mass and filter backpressure evolution with time during loading processes, in which soot particle sizes varied, with the aim to analyze how particulate size affects the filter pressure drop rise. A wall-flow filter was investigated, and the behavior of clean material was evaluated by a parametric analysis in which particle diameter varies in the filed 20−1000 nm, that is the typical range of soot sizes in diesel engine exhaust. The results demonstrate that soot size has a great influence on the initial deep bed loading process. Moreover, it defines the value from which the linear pressure drop shape during cake filtration starts, not only when the initial loaded is completed, but also each time the regeneration event is concluded. This outcome provides an important guideline to define the most appropriate strategy for the initial DPF loading in order to establish the regeneration event based on the estimation of trapped mass accounting for the filter backpressure and on the time interval between two successive regeneration.